Propagasi In Vitro Kaliandra Merah (Calliandra calothyrsus Meisn.) II: Induksi Perakaran Tunas dan Aklimatisasi Planlet - Muhammad Idris; Auzia Asman; Deni Sorel; Edi Joniarti; Ulfa Mohtar; Harmailis Harmailis; John Nefri; Salvia Salvia (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Red calliandra is one of woody plants that has been extensively developed as biofuel. Tissue culture techniques are employed to produce a large and uniform quantity of seedlings in a relatively short period. Previous stages of in vitro initiation and multiplication of shoot from calliandra explants have shown promising results. The shoots that were multiplied by in vitro technique need to be induced for rooting process to produce plantlets. These plantlets are then prepared for the subsequent acclimatization process. This research was conducted in two stages; root induction of shoots using a modification of MS half-strength media (MS ½) supplemented with 1-4 mg/L 1-naphthaleneacetic acid (NAA), and acclimatization of the plantlets into soil media. The results shown that MS ½ medium and media supplemented with 1 mg/L NAA were suitable for root induction, particularly to induce the root length. Furthermore, MS ½ media supplemented with 1-2 mg/L NAA stimulates the increment of plantlet height and leaves numbers. Plantlets which were transferred into soil exhibit robust growth during 3-weeks of acclimatization process, up to 100% plantlets survived during this stage. These results underscore the potential of tissue culture techniques in providing large scale calliandra seedlings production for future biofuel development.